Tonga : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper reviews economic developments in Tonga during 1990-95. During 1990/91-1991/92, GDP rose by an average of 3.4 percent, fueled by a fourfold increase in squash exports. In 1992/93, GDP growth quickened to 3.7 percent, largely on the basis of a rebound in construction and a rise in domestically oriented manufacturing production-and despite a sharp fall in squash exports. In 1993/94, growth reached 4.7 percent, as squash exports again increased, construction boomed, and commerce accelerated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet